Effect of NiTi matrix grain size on the ultra-large elastic deformation of V nanowires in a V/NiTi composite. (December 2021) - Yao, Xudong; Tang, Wang; Sun, Zhonghui; Shi, Xiaobin; Wang, Yongqiang; Li, Yongtao; Jiang, Jiang; Zhang, Junsong
Abstract: A vanadium nanowires/NiTi composite was fabricated by forging and drawing a Ni38 Ti37 V25 alloy and effect of NiTi matrix grain size on the elastic deformation of V nanowires in composite was investigated. The results revealed that NiTi grain size increased with the increasing annealing temperature, however, morphology of V nanowires was independent of annealing temperature. The in situ synchrotron X-ray diffraction studies revealed that V nanowires in the composite exhibited ultrahigh lattice strain during tension loading and the maximum lattice strain decreased with the increasing NiTi matrix grain size. This grain size effect is mainly attributed to the lattice strain mismatch at V/NiTi interface and inhomogeneity of stress distribution in NiTi matrix. The findings of this work provide a theoretical basis for the design of novel nanowire composites.